Bitter Taste Receptors as Regulators of Abdominal Muscles Contraction - Zagorchev, P; Petkov, G V; Gagov, H S (Physiological research, 2019)
Bitter taste receptors (TAS2R) are expressed in many non-sensor tissues including skeletal muscles but their function remains unexplored. The aim of this study is to investigate the role of TAS2R in rat abdominal skeletal muscles contractions using denatonium, a TAS2R agonist. Low concentration of denatonium (0.01 mmol/l) caused a significant decrease of amplitudes of the electrical field stimulation (EFS)-induced contractions in abdominal skeletal muscles preparations in vitro. This inhibitory effect was significantly reduced when the preparations were pre-incubated with gentamicin (0.02 mmol/l) used as a non-specific inhibitor of IP3 formation or with BaCl(2) (0.03 mmol/l) applied to block the inward-rectifier potassium current. All experiments were performed in the presence of pipecuronium in order to block the nerve stimulation of the contractions. The data obtained suggest that denatonium decreases the force of rat abdominal muscles contractions mainly via activation of TAS2R, phosphatidylinositol 4,5-biphosphate and its downstream signal metabolites.
Keywords: Receptors, G-Protein-Coupled; svalová kontrakce; gentamiciny; Muscle Contraction; Organ Culture Techniques; břišní svaly; orgánové kultury - kultivační techniky; chuť; krysa rodu Rattus; zvířata; Gentamicins; potkani Wistar; Abdominal Muscles; Rats, Wistar; Male; Taste; chuťový receptor typu 2; Taste Receptors, Type 2; Rats; Animals; mužské pohlaví; receptory spřažené s G-proteiny